Overview of storage energy systems for renewable energy system application - Yunus, A.; Alharbi, Yasser; Abu-Siada, Ahmed; Masoum, Mohammad Sherkat (Depertsnent of Electrical Engineering, faculty of Engrineering, University of Hasanuddin, 2012)
The integration of renewable energy system into modern power grids has significantly increased during the last decade. Solar and wind energy are the most popular renewable energy sources recently. Solar energy has reached about 17,3 GW in 2010 whilst about 340 TWh of wind energy source has been installed worldwide. In this paper, the overview of updated information regarding proposed storage energy systems for renewable energy is presented. It is useful information for practitioners in considering the possible options of storage energy technologies to be connected with renewable energy sources.